1977
DOI: 10.1254/jjp.27.47
|View full text |Cite
|
Sign up to set email alerts
|

Effect of Clonidine on Blood Pressure, Heart Rate and Body Temperature in Conscious Rats

Abstract: Abstract-Effects of clonidine on blood pressure, heart rate and rectal temperature in conscious rats were examined. Clonidine (0.1-1 mg/kg s.c.) caused a prevailing pressor response and dose-dependently a fall in heart rate and body temperature.The pressor response to clonidine (0.3 mg/kg s.c.) was completely reduced by phentolamine (10 mg/kg s.c.), chlorpromazine (10 mg/kg s.c.) but not by hexamethonium (30 mg/kg i.p.), guanethidine (30 mg/kg s.c.) or reserpine (5 mg/kg s.c. 18 hr+ 1 mg/kg i.p. 4 hr prior to … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1

Citation Types

1
1
0

Year Published

1979
1979
2023
2023

Publication Types

Select...
6
1

Relationship

0
7

Authors

Journals

citations
Cited by 31 publications
(3 citation statements)
references
References 25 publications
(24 reference statements)
1
1
0
Order By: Relevance
“…2E). While clonidine, administered at a dose known to alter HR and body temperature (40), induced activation of LC NE neurons increased pupil dilation, as previously reported (41), LC Ex-4 had no effect on pupil to iris ratio (Fig. 2F).…”
Section: Lc Glp-1r Activation Drives Select Autonomic Responsessupporting
confidence: 82%
“…2E). While clonidine, administered at a dose known to alter HR and body temperature (40), induced activation of LC NE neurons increased pupil dilation, as previously reported (41), LC Ex-4 had no effect on pupil to iris ratio (Fig. 2F).…”
Section: Lc Glp-1r Activation Drives Select Autonomic Responsessupporting
confidence: 82%
“…Other effects of clonidine were a decrease in body temperature, which has been shown to be due to a central action on a 2adrenoceptors (34,35). Clonidine given as a high bolus dose has been shown to cause respiratory depression and severe hypoxemia in sheep (36), but this effect was not seen with infusion of clonidine in septic sheep.…”
Section: Effects On Cytokinesmentioning
confidence: 99%
“…For instance, while NA or the a2-agonist clonidine (CLON) lower body temperature in mice and rats (Brittain and Handley, 1967;Bugajski and Zacny, 1980;Laverty and Taylor, 1969;Ozawa et al, 1977), opposite effects occur in rabbits (Cooper et al, 1965). Moreover, it was found that temperature changes produced by noradrenergic stimulation are dependent upon ambient temperature (AT).…”
Section: Introductionmentioning
confidence: 99%